2013
DOI: 10.5999/aps.2013.40.4.374
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of CG CryoDerm and AlloDerm in Direct-to-Implant Immediate Breast Reconstruction

Abstract: BackgroundTo date, various types of acellular dermal matrix (ADM) have been developed for clinical use. AlloDerm is the most familiar type of ADM to most surgeons in breast reconstruction. It is prepared by freeze-drying. CG CryoDerm is the first form of ADM that requires no drying process. Therefore, theoretically, it has a higher degree of preservation of the dermal structures than AlloDerm. We conducted this study to compare the clinical course and postoperative outcomes of patients who underwent direct-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Of the 40 comparative studies, the majority were retrospective (37), single‐centre (36) studies that reported the outcomes of two‐stage expander–implant reconstruction with and without ADM (25). Nine studies compared different types of ADM; three specifically evaluated the impact of radiotherapy on ADM‐assisted reconstruction, and five evaluated different aspects of the procedure including ADM size, antibiotic regimens, incision placement and single‐ versus two‐stage procedures. The median sample size was 63 (i.q.r.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 40 comparative studies, the majority were retrospective (37), single‐centre (36) studies that reported the outcomes of two‐stage expander–implant reconstruction with and without ADM (25). Nine studies compared different types of ADM; three specifically evaluated the impact of radiotherapy on ADM‐assisted reconstruction, and five evaluated different aspects of the procedure including ADM size, antibiotic regimens, incision placement and single‐ versus two‐stage procedures. The median sample size was 63 (i.q.r.…”
Section: Resultsmentioning
confidence: 99%
“…It was unclear how patients were selected for ADM versus standard submuscular procedures, with only one-third (22) reporting these details. Four 62,68,75,85 compared IBBR with and without ADMs conducted during consecutive time periods, three studies 66,67,71 used ADMs (or not) based on surgeons' preferences, three studies 12,59,76 reported that the decision to use ADM was made during surgery based on mastectomy skin-flap thickness, and one study 81 compared different surgeons' practices. These studies were therefore at high risk of selection bias and confounding, and the groups were not directly comparable.…”
Section: Non-randomized Studiesmentioning
confidence: 99%
“…Alloderm® has been used in various reconstructive surgery since 1995, and there are many multivariate studies on complications in soft tissue reconstruction. 24 , 25 , 26 The major complaints of Alloderm® are bulkiness and depression of the tip and the dorsum. In specific cases, we recommend the use of Alloderm® to camouflage the gap at the supratip.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these products vary in many ways, depending on the source of tissue material, manufacturing methods, storage and surgical preparation, available size, and cost. However, their use is often limited due to the lack of outcome data [ 26 , 27 ]. Moreover the most recent major retrospective studies have demonstrated an high rates of complications such as infection, seroma formation, capsular contracture, implant exposure that needs reoperation with the above matrices.…”
Section: Discussionmentioning
confidence: 99%
“…BIOSILK™ purification removes impurities leaving an ultrapure bioprotein designed to provide an improved and consistent user experience. Operatively SERI® can be cut without unravelling, is easy to suture (large pores), does not require refrigeration or rehydration as the surgical ADM scaffold previously described [ 27 , 28 ]. Our experience reported start on April 2013 until May 2014, it is based on 21 cases of direct to implant (DTI) breast reconstruction after SSM (9 monolateral 6 bilateral) by using SERI as surgical scaffold to envelope the implant for inferior/lateral pole coverage.…”
Section: Discussionmentioning
confidence: 99%